Praetorianistic Behavior Forms: An Investigation of School Principals - Baltacı, Ali (My University, 2019)
Praetorianism is an administration system where the military takes an active role in political decisions openly or covertly. The purpose of this study is to determine the levels of school principals' praetorianistic behavior. This research was designed with a descriptive scanning model. The target universe of the research includes 370 school directors working in state and private secondary schools in 25 districts of Ankara. In the research, the entire universe was reached and a "complete counting" technique was used. Data of the study were obtained using the praetorianism scale developed by the researcher. The data were analyzed using descriptive statistical methods. According to the results of the study, the most praetorianistic behavior of the school principals' is 'helpfulness'. However, 'authoritarianism', 'sordidness', 'compelling', ‘negative criticism’, and 'orientation' are the praetorianistic behaviors of school principals. The praetorianistic behaviors of school principals differ significantly according to the variables of gender, educational status, school type, and sector. On the other hand, it has been determined that professional tenure does not differentiate between praetorianistic behaviors.

Praetoryanizm, askeri veya sivil otoritelerin siyasi ve sosyal kararlarda açık veya gizli olarak aktif bir rol aldığı vesayete dayalı bir yönetim sistemidir. Bu çalışmanın amacı, okul müdürlerinin praetoryanist davranış biçimlerini gösterme düzeylerinin belirlenmesidir. Bu araştırma, betimsel tarama modeli ile tasarlanmıştır. Araştırmanın hedef evrenini, Ankara ilinin 25 ilçesinde resmi ve özel ortaöğretim okullarında görev yapmakta olan 370 okul müdürü oluşturmaktadır. Araştırmada evrenin tamamına ulaşılarak, “tam sayım” tekniği kullanılmıştır. Çalışmanın verileri, araştırmacı tarafından geliştirilen praetoryanizm ölçeği kullanılarak elde edilmiştir. Veriler, betimsel istatistik yöntemleri kullanılarak analiz edilmiştir. Çalışma sonuçlarına göre, okul müdürlerinin en çok sahip oldukları praetoryanist davranışın ‘yardımseverlik’ olduğu sonucuna ulaşılmıştır. Bununla birlikte 'otoriterlik', 'yararcılık', ‘zorlayıcılık', ‘olumsuz eleştiri’, ‘sınırlayıcılık ve 'yönlendiricilik' de okul müdürlerinin sahip olduğu praetoryanist davranışlardandır. Okul müdürlerinin praetoryanist davranışları, cinsiyet, eğitim durumu, okul türü ve eğitim kolu (sektör) değişkenlerine göre anlamlı bir şekilde farklılaşmaktadır. Buna karşın mesleki kıdemin praetoryanist davranışları farklılaştırmadığı belirlenmiştir.
Praetoryanist Davranış Kalıpları: Okul Müdürleri Üzerine Bir İnceleme